Meningkatkan Kemampuan UMKM Kecamatan Cibadak Kabupaten Lebak Banten Melalui Workshop Sistem Daya Saing (Pelatihan Accounting, Pricing, dan Marketing Berbasis Web) - Wahyudi Wahyudi; Yoko Tristiarto; Yul Tito Permadhy; Anita Nopiyanti (IKRA-ITH ABDIMAS, 2023)
The lack of solid Indonesian economic fundamentals has prompted the government to buildan economic structure by taking into account the existence of Micro, Small and MediumEnterprises (SMEs). This sector has been proven to provide jobs and provide opportunities forSMEs to develop in society. The existence of SMEs cannot be doubted because they have proven tobe able to survive and become an economic driver, especially after the economic crisis. On theother hand, SMEs also face many problems, namely limited working capital, low humanresources, and inadequate mastery of science and technology. Another obstacle faced by MSMEsis the unclear relationship with business prospects and unstable planning vision and mission.Providing information and market networks, easy access to funding and assistance as well asincreasing information technology capacity are some strategies to increase the competitiveness ofIndonesian SMEs.In this case, special attention is needed for SMEs, especially for business records,determining HPP and marketing problems. Efforts to develop small and medium industries, thenthese weaknesses must be overcome. This is where the role of universities as educationalinstitutions can be more involved and help overcome existing problems so that it is hoped thatMSMEs can continue to play a role in Indonesia's economic growth and development.